Designer tubers for production of novel compounds - Sonnewald, Uwe; et al. (2003)
Based on world-wide efforts to identify novel biopharmaceuticals, numerous low (metabolites) and high (proteins) molecular weight compounds have been described which, when used for clinical treatments, would offer substantial improvements for today's clinical therapies. As the demand for biopharmaceuticals is expected to exceed their availability, safe and cost-effective production systems are urgently needed. Plants offer several advantages over conventional production systems, but contamination of food- or feedstuff must be avoided. This can be achieved by applying inducible gene expression systems. In contrast to dry seeds, potato tubers remain metabolically active throughout the storage period, which makes them ideal as a bioreactor for biopharmaceuticals. Using a chemically inducible gene-switch post-harvest accumulation of biomolecules can be obtained, offering the possibility to grow non-pharmaceutical containing tubers in the field. To allow post-harvest induction of pharmaceutically relevant polypeptides an ethanol inducible gene switch for potato tubers has been established and optimized. As an example for the production of an edible vaccine the papillomavirus (HPV) major capsid protein L1 has been chosen. Since cervical cancer is linked to infection with HPV and is the third most common cancer among women world-wide, there is a strong demand for the development of an HPV preventive vaccine. The plant-derived L1 protein displayed conformation-specific epitopes and assembled into virus-like particles. In addition to unintended contamination of food- or feedstuff with biopharmaceuticals, unauthorized distribution of seed tubers must be avoided. Since potato plants can easily be propagated in tissue culture, the use of non-sprouting tuber bearing potato varieties offers a possible strategy to restrict seed tuber distribution. Based on current biochemical and molecular knowledge transgenic potato plants producing non-sprouting tubers for restricted production of biopharmaceuticals have been designed by interfering with long-distance sucrose transport. Combining inducible gene expression systems and nonsprouting tubers should strongly improve public acceptance of GM potatoes for the production of edible vaccines or non-plant metabolites.